PENGEMBANGAN KAMPUNG SENI DAN BUDAYA DESA SENDANGASRI MENJADI DESA WISATA - Muhammad Tahwin; Anik Nurhidayati (Buletin Abdi Masyarakat, 2021)
As the partner of the community dedication is Sendangasri the art and cultural village in Rembang Regency. The problems faced by the partner are (1) Management of art and cultural has not been established, (2) The village does not have the managerial ability, (3) The village has not made use of art and cultural website as the promotion media, (4) The village does not have attractive supporting facility. Therefore, the purpose of the dedication program is to improve the human resources in managing the tourism village, giving good service and promoting the existence widely. The method used in carrying out the program is training and mentoring. The result show (1) The forming of tourism village board based on Sendangasri villager’s decision: 14/I/2020, on September 21nd, 2020, (2) Improving partner’s knowledge and ability in tourism management, (3) able to update the website with interesting content and information. (4) Partner start to build the spots that supporting art and cultural tourism destination. Keywords: Tourism Village, Training, Mentoring, Website